The future will not be Protestant - Mariano, Ricardo (1999)
This paper discuss, from the brazilian case, the idea which Latin America is turning protestant. It disagrees the “protestant explosion” has potencial to transform the culture and to modernize Latin-American economy. It shows numerical decline of the traditional protestantism and the pentecostalism vertiginous growth. This work defends the thesis that pentecostalism does not carry modernizing virtualities contained into the calvinist ethic analysed by Weber. It argues pentecostalism is promoting successives social accomodations, and it is turning into a religion less and less ascetic, sectarian, distinctive, and, therefore, more vulnerable to brazilian anthropophagy.